Nifedipine in controlling blood pressure in severe pre-eclampsia - eclampsia. - Tapia Silva, Luis (2015)
The severe preeclampsia-eclampsia is a major cause of morbidity and mortality in Latin America and the world. At Regional Hospital of Trujillo, it was observed between 1976-1984, that patients with this diagnosis 5% died and the remaining 30% showed any of the following complications: bronchopneumonia, acute pulmonary edema, placental abruption, acute kidney failure and others. The newborns were stillborn 13.95% and 51% of the remaining had some degree of neonatal asphyxia. Severe hypertension observed in these cases (greater than 160/110 mmHg), is directly related to these complications.